Turkish Version of the Jefferson Scale of Empathy Psychometric Properties - Bilgel, Nazan; Ozcakir, Alis (European Scientific Journal, ESJ, 2017)
Empathy is an important component of medical education and could be taught throughout the years of medical study. Empathy is a skill that allows establishing a communication by evaluating the views, experiences and worries of the patientsâ€™ cognitively. Empathy can improve physicianpatient communication, increase patient satisfaction, establish greater patient compliance, decrease litigation, improve physicianâ€™s job satisfaction and prevent physicianâ€™s burnout. Therefore measurement of this skill is important. Jefferson Scale of Empathy is an instrument for this purpose and has been translated into 45 languages and used in more than 70 countries. The objective of this study was to evaluate the reliability and construct validity of the Jefferson Scale of Empathy Turkish version. The scale was administered to 600 medical students in one medical school. Cronbachâ€™s alpha coefficient of the Jefferson Scale of Empathy was 0.85 which means a good reliability. Competing models of the latent structure of the Jefferson Scale of Empathy were derived from theoretical and empirical sources and evaluated using confirmatory factor analysis. The best fitting model of the latent structure of the Jefferson Scale of Empathy consisted of three correlated factors corresponding to the â€œperspective takingâ€, â€œcompassionate careâ€ and â€œstanding in patientâ€™s shoesâ€ dimensions. The reliability coefficients of these dimensions were 0.84, 0.73 and 0.62 respectively. The Turkish version of the Jefferson Empathy Scale is a reliable and valid measure of the constructs it was intended to assess. This measure was found useful for evaluating empathy among medical students